Does the school environment exert influence on quality of life related to traumatic dental injury in children? - Maritza Del Carmen QUEZADA-CONDE; Patricia Lourdes ALVAREZ-VELASCO; Mariela Cumanda BALSECA-IBARRA; Raíza Dias FREITAS; Thiago Machado ARDENGHI; Edgard MICHEL-CROSATO; Claudio Mendes PANNUTI; Antonio Carlos FRIAS; Daniela Prócida RAGGIO; Fausto Medeiros MENDES (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The aim of this cross-sectional study was to assess whether favorable factors related to school characteristics have a positive effect on the impact of traumatic dental injury (TDI) on oral health-related quality of life (OHRQoL). An epidemiological survey of oral health was conducted with 12-year-old schoolchildren from Quito, Ecuador. Children were examined for TDI, dental caries, and malocclusion. Individual socioeconomic data were also collected. Information on the physical environment, health practices, and occurrence of negative episodes at school was collected from the school coordinators. The Child Perceptions Questionnaire 11-14 (CPQ11-14) was used to evaluate the OHRQoL (outcome variable). Multilevel Poisson regression analysis was conducted. Severe TDI was associated with higher CPQ11-14 scores, even in the multiple model adjusted for oral health conditions, sex, individual socioeconomic variables, and school-related variables. Children from schools that had an appropriate tooth-brushing environment for their students exhibited a lower impact on OHRQoL, even after adjustment for the occurrence of TDI and other variables. A favorable school environment may exert a positive effect on OHRQoL, independent of the occurrence of TDI.